Radar Technology for Coastal Areas and Open Sea Monitoring - Ludeno, Giovanni; Uttieri, Marco; Ludeno, Giovanni; Uttieri, Marco (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Monitoring oceans and coastal areas has a fundamental social impact, and this scenario is made still more challenging with the present and future issues related to climate change. In this context, radar systems have gained increasing interest, since they are remote sensing devices capable of providing information about sea waves, currents, tides, bathymetry, and wind. Moreover, radar systems can be designed to perform both large-scale and small-scale monitoring, with different spatial and temporal resolutions, and can be installed on different observation platforms (ship-based, ground-based, airborne, satellite or drones). In this regard, this book aims at engendering a virtual forum for ocean radar researchers, where state-of-the-art methodologies and applications concerning ocean monitoring by means of radar technologies are reviewed and discussed.
English
Keywords: History of engineering & technology; HF radar; monitoring; circulation; Atlantic Jet; flow reversal; Gibraltar; Alboran Sea; X-band radar; tidal variation; modified temporal waterline method; shoreline position; intertidal foreshore slope; wave run-up correction; current velocity measurement; high-frequency (HF) radar oceanography; remote sensing; quality control; coastal surface currents; soft computing; radar; sensitivity experiments; numerical model; artificial neural network; inversion; radar cross-section; monostatic radar; ocean wave directional spectrum; TensorFlow; wave directional spectra; spatial wave fields; ADCP; wave buoy; significant wave height; marine radar; sea state monitoring; scum; hypertrophic ecosystem; Sentinel-1; Sentinel-2; Sentinel-3; cloudiness; high-frequency ocean radar; interference mitigation; frequency band adaptation; high frequency radar; sea surface temperature; surface currents; south-west Australia; synthetic aperture radar; Doppler anomaly; sea surface currents; Gulf of Naples; augmented observatory; wave field; radar Doppler altimeter; orbital velocities; waveforms; swell; radar altimeter